VIEWER RECEPTION TOWARD YOUTUBER'S GIVEAWAY - Dyva Claretta; Marta Wijayanengtias (Universitas Islam Balitar, 2021)
Lately Youtuber is one of the favorite professions by people because easy to getting money from uploading videos that generate Adsense. The amount of Adsense that you get depends from account owners traffic, that is the number of viewers on the video uploaded. This makes Youtubers use their brain more creative to promoting their channel with giveaway as the way. However, when something becomes a trend, there will be various reactions from the audience. For example, news about suspicion about Youtubers who give fake giveaways, giveaway law in islam, videos of giveaway reactions by Youtubers, how to get giveaways from Youtuber and many more. From the many pros and cons, the reason based on the main goal of Youtuber making giveaway to get Adsense, makes value of the video ignored. So that video Is considered less education and seems just s setting. From this respons, the researcher wants to know how the viewer receptions about giveaway trend that youtuber doing lately using Stuart Hall’s theory. The results of this qualitative descriptive study found that the viewer’s reading position is negotiated reading because they accept the existing giveaway trends, but they are quite selective and have their own standart to join giveaway and choosing Youtube videos.